Kemampuan Pemecahan Masalah Matematika ditinjau dari Komunikasi Matematis Siswa Kelas IX SMPN 1 Batulayar - Harman, Muafira; Sripatmi, Sripatmi; Tabita Wahyu Triutami; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2024)
This research aims to describe the ability to solve mathematical problems in terms of the level of mathematical communication skills of class IX students at SMPN 1 Batulayar for the 2023/2024 academic year. The type of research used is descriptive qualitative. Based on the results of data analysis, students with high mathematical communication skills were able to fulfill several indicators of problem-solving ability, such as the second and third indicators correctly, although there were students who were able to fulfill the first indicator on several questions. For mathematical communication skills, students in the moderate category are able to fulfill several problem-solving indicators, such as the second and third indicators, although they are not yet complete, but are not yet able to fulfill the first and fourth indicators. Meanwhile, students with low mathematical communication skills have not been able to fulfill the four indicators of mathematical problem-solving abilities.